(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
The aim of this research is to examine the impact of unethical leadership on job embeddedness with in Pakistan’s banking sector, scrutinizing the role of perceived organizational support as a moderator and workplace ostracism as a mediator. The principle of Social Exchange and Conservation of Resources Theory were used to propose the hypotheses of this study. A Sample of 543 employees was collected from banking sector in Pakistan, which was analyzed by utilizing the SPSS and R project for reliability, validity of the instrument and statistical analysis. Results reveal a direct negative link between unethical leadership and job embeddedness. Workplace ostracism mediates this relationship, indicating that unethical leadership impacts job embeddedness through ostracism. Further, POS moderates this negative relationship acting as a buffering mechanism. This research contributes to the understanding of how unethical leadership affects job embeddedness by integrating the roles of workplace ostracism and perceived organizational support. It provides valuable insights for banking sector leaders and policymakers to develop strategies that promote ethical behavior and the role of perceived support in mitigating the adverse effects of unethical leadership, thereby offering practical implications for positive leadership practices and perceived support in the banking sector.